Comparison of routing algorithms for storage and retrieval mechanism in cylindrical AS/RS - Janilionis, Vytautas V.; Bazaras, Žilvinas; Janilionis, Vytautas (Transport, 2016)
The objective of this research is to propose new routing algorithms for the Storage and Retrieval Mechanism (SRM) in the Cylindrical Automated Storage and Retrieval System (C-AS/RS) and contribute to the system conceptualization by investigating the maximum achievable retrieval request rates for different routing algorithms and system parameters. For this purpose, flexible and detailed simulation model was developed and investigated for 2 SRM types, 3 routing algorithms and a feasible set of system movement and load transfer time parameters. Based on the simulation output, the regression models for different SRM types and routing algorithms were developed for predicting the maximum retrieval request rate. The differences of the average maximum retrieval request rate were evaluated for various system configurations and routing algorithms. The alternative to optimal routing algorithm was proposed, reducing the system performance only by 1.4÷2.4% on average, but requiring significantly less calculations when planning the SRM tour. In addition, the system analysis indicated that SRM vertical velocity and load transfer time have the highest impact on the system performance and for different SRM types the average maximum retrieval request rates differ by 22.2÷31.8%. First published online: 14 Jan 2015